Judging prosecutors: Public support for prosecutorial discretion - Michael J. Nelson; Taran Samarth (Research & Politics)
Prosecutors have immense discretion to determine which offenses to charge, which cases to take to trial, and which sentences to recommend. Yet, even though many of the prosecutors who exercise this discretion over important crimes must face the electorate to keep their jobs, we know little about how the use of this discretion affects prosecutors’ electoral fortunes. Drawing on two experiments embedded in a nationally representative survey, we demonstrate that the public is more supportive of prosecutors who issue lenient sentences for low-level crimes. The results have important implications for criminal justice reform inasmuch as they provide a linkage between progressive prosecutorial behavior and respondents’ vote intentions.